Rainbow Vertex Connection Number pada Keluarga Graf Roda - Firman Firman; Dafik Dafik; Ermita Rizki Albirri (CGANT JOURNAL OF MATHEMATICS AND APPLICATIONS, 2022)
The rainbow vertex connection was first introduced by krivelevich and yuster in 2009 which is an extension of the rainbow connection. Let graph $G =(V,E)$ is a connected graph. Rainbow vertex-connection is the assignment of color to the vertices of a graph $G$, if every vertex on graph $G$ is connected by a path that has interior vertices with different colors. The minimum number of colors from the rainbow vertex coloring in graph $G$ is called rainbow vertex connection number which is denoted $rvc(G)$. The result of the research are the rainbow vertex connection number of family wheel graphs.